Upaya Pencegahan Kekerasan Seksual melalui Konten Edukasi Seksual bagi Anak Pekerja Migran Indonesia di Sanggar Belajar Kepong Malaysia - Arqiya, Safiya; Dahnial, Irfan (Jurnal Gentala Pendidikan Dasar, 2026)
This study aims to evaluate the effectiveness of sexual education content at the primary education level as a preventive effort against sexual violence toward children of Indonesian migrant workers (IMWs). The study is motivated by the high risk of sexual violence faced by IMW children due to limited parental supervision, unstable family environments, and restricted access to early sexual education, which results in low understanding of body autonomy, safe and unsafe touch, and self-protection strategies. This research employed a quantitative method using a pretest–posttest design supported by qualitative data from interviews. The research subjects consisted of 25 primary school students who are children of Indonesian migrant workers, with interactive sexual education content as the research object. Data were collected through questionnaires, tests, observations, and interviews, and analyzed using validity and reliability tests, descriptive statistics, and the Wilcoxon Signed Rank Test. The results indicate that the instruments were valid and reliable (Cronbach’s Alpha = 0.914) and that there was a significant increase in children’s knowledge after the implementation of sexual education content. Therefore, sexual education content is proven to be an effective preventive strategy in nonformal education settings.